COMMUNICATION STRATEGY IN ENGLISH LANGUAGE LEARNING (AN ETHNOGRAPHY RESEARCH IN INTERNATIONAL SCHOOL OF AIScho BSD City) - Arif Rahman (Jurnal Ilmiah Mandala Education (JIME), 2017)
This study aims to examine how communication strategies in English language learninge emloyed by learners in SMP international as an effort to ensure that the messages are conveyed to the listener. Futhermor, this study inverstigates the uses of verbal communication strategy dan nonverbal communication strategy in language learning of international school students. This research conducted a qualitative approach with an ethnography method.  The data of 27 learners’ spoken speech were collected from observation by using audio recorder, field notes and unstructured interview. The data analisis were using performance analysis technique, a futher analysis based on actual speeches and linguistic behaviors.The analysis reveals that the learners employ communication strategies in English language learning consists of verbal communication strategy and nonverbal communication strategy. The finding futher shows that the learnes employ both communication strategies in terms of three reasons; the use of communication strategies as a systematic technique to convey certain messages that can assist students in improving their communication in the target language to convey language competence, and strategic competence